2006
DOI: 10.1083/jcb.200506179
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion size controls tension-dependent recruitment of α-smooth muscle actin to stress fibers

Abstract: Expression of α-smooth muscle actin (α-SMA) renders fibroblasts highly contractile and hallmarks myofibroblast differentiation. We identify α-SMA as a mechanosensitive protein that is recruited to stress fibers under high tension. Generation of this threshold tension requires the anchoring of stress fibers at sites of 8–30-μm-long “supermature” focal adhesions (suFAs), which exert a stress approximately fourfold higher (∼12 nN/μm2) on micropatterned deformable substrates than 2–6-μm-long classical FAs. Inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
620
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 651 publications
(656 citation statements)
references
References 66 publications
35
620
1
Order By: Relevance
“…The morphologies of the stamps used for patterning were shown in Fig. 1a-c. Pattern L20 (12,6) consisting of rectangular islets of size 20 · 2 mm was designed to induce elongated FA according to a previous report [18]. We optimized the vertical spacing by changing it from 6 to 12 mm to guide cell growth along the direction of a higher ECM density, that is, denser islet to form elongated FA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphologies of the stamps used for patterning were shown in Fig. 1a-c. Pattern L20 (12,6) consisting of rectangular islets of size 20 · 2 mm was designed to induce elongated FA according to a previous report [18]. We optimized the vertical spacing by changing it from 6 to 12 mm to guide cell growth along the direction of a higher ECM density, that is, denser islet to form elongated FA.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are limited studies using FA modulation to induce stem cell differentiation. Among these, Goffin et al employed micropatterning to modulate FA development in myofibroblasts and found that the FA length controls the transition of smooth muscle actin (SMA) into stress fibers in a tension-dependant manner [18]. Seo et al found that FA maturation and actin polymerization were promoted via the RhoA pathway when MSCs were cultured on microtopographical substrates [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in substrate stiffness have been shown to significantly alter the actin cytoskeleton and focal adhesions (FAs) of a range of cell types, including fibroblasts, mesenchymal stem cells, endothelial cells, and chondrocytes (Goffin et al 2006;Engler et al 2006;Byfield et al 2009;Schuh et al 2010). Different ranges of substrate stiffness that influence cytoskeletal remodelling have been reported for different cell phenotypes; particularly, more contractile cells, such as myoblasts, are most sensitive up to ~400 kPa (Ren et al 2008), but less contractile cells, such as fibroblasts, are sensitive up to ~20 kPa (Yeung et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Different ranges of substrate stiffness that influence cytoskeletal remodelling have been reported for different cell phenotypes; particularly, more contractile cells, such as myoblasts, are most sensitive up to ~400 kPa (Ren et al 2008), but less contractile cells, such as fibroblasts, are sensitive up to ~20 kPa (Yeung et al 2005). Previous in-vitro studies have quantified the effect of different substrate stiffness on stress fibre (SF) formation (Solon et al 2007), FA area (Goffin et al 2006), cell traction (Califano and Reinhart-King 2010), and cell shape (Yeung et al 2005). However, the cellular mechanisms underlying these phenomena are poorly understood.…”
Section: Introductionmentioning
confidence: 99%